Knowledge, Attitudes, and Practices of Dental Students from Romania Regarding Self-Perceived Risk and Prevention of Infectious Diseases - Florentina Iuliana Dincă; Bogdan-Alexandru Dimitriu; Oana Săndulescu; Valentin Daniel Sîrbu; Mihai Săndulescu (MDPI AG, 2024)
University education is a leading source of information for dental practitioners. Particular emphasis should be given to determining the extent to which students acquire positive knowledge, attitudes, and practices (KAP) and positive metacompetences beyond the scope of each studied dental discipline. We performed a cross-sectional questionnaire-based study among dentistry students from Romania to assess self-perceived risk of infectious diseases and their KAP on topics related to infectious disease prevention. The surveyed students presented good knowledge regarding personal protective equipment (PPE), and their PPE practices significantly correlated with the perceived usefulness of PPE. Only 45.1% correctly recognized all vaccine-preventable diseases (VPDs), but knowledge regarding VPDs significantly improved with increasing year of study (τb = 0.298, p = 0.001), confirming a positive education effect. Awareness regarding the need for screening for bloodborne viruses is poor; the majority of students had never performed a test for hepatitis C virus infection (HCV) (59.4%) or for human immunodeficiency virus (HIV) infection (60.4%). Furthermore, most respondents incorrectly considered themselves at high or very high risk of acquiring BBV, and perceived risk was inversely correlated with willingness to treat patients with hepatitis B virus (HBV) infection (τb = −0.214, p = 0.018), HCV infection (τb = −0.234, p = 0.013), or HIV infection (τb = −0.242, p = 0.006). This led to 3.0% of respondents stating that they would hypothetically deny dental treatment to a patient with HBV infection, 5.0% for HCV infection, and 10.9% for HIV infection, the proportion being significantly higher for HIV (z = −2.2, p = 0.026). In conclusion, better knowledge is needed among dental students regarding their own vaccination history, screening for bloodborne viruses, accurate estimates for their risk of acquiring bloodborne viruses during routine dental practice, and the existence of post-exposure measures following occupational exposure. Improving student knowledge and awareness could translate into a higher willingness to treat patients with chronic viral infections and into a safer and more inclusive dental practice. We propose an adaptation to the university curriculum to cover these key areas for targeted focus to empower future dental practitioners and to facilitate the improvement of across-discipline metacompetences for infection prevention and control.